Rate of convergence of bounded variation functions by a Bézier-Durrmeyer variant of the Baskakov operators. (3rd March 2004) - Gupta, Vijay; Abel, Ulrich
Abstract : We consider a Bézier-Durrmeyer integral variant of the Baskakov operators and study the rate of convergence for functions of bounded variation.